2016
DOI: 10.1089/cbr.2015.1956
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding Epidermal Growth Factor-Like Growth Factor as a Potent Target for Breast Cancer Therapy

Abstract: Heparin-binding epidermal growth factor-like growth factor (HB-EGF) belongs to the EGF family and exhibits its activity after binding to its receptors in autocrine, paracrine, and juxtacrine interactions. HB-EGF plays important roles in several biological and pathological processes, such as wound healing, blastocyst implantation, atherosclerosis, and heart development. Clinical studies have shown that HB-EGF is closely correlated with tumorigenesis, metastasis, and drug resistance in breast cancer. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Growth factor binding is found in the progression of various cancers. For example, heparin-binding epidermal growth factor-like growth factor acts as a potent target for breast cancer therapy [23]. Voltage-gated Na+ channel…”
Section: Discussionmentioning
confidence: 99%
“…Growth factor binding is found in the progression of various cancers. For example, heparin-binding epidermal growth factor-like growth factor acts as a potent target for breast cancer therapy [23]. Voltage-gated Na+ channel…”
Section: Discussionmentioning
confidence: 99%
“…Paracrine signalling is a main form of intercellular communication, by which cells respond to the factors produced from nearby cells [ 26 , 27 ]. It has been shown that HB-EGF plays a variety of roles in cell proliferation, migration and inflammation through paracrine action [ 28 , 29 ]. Whether such a paracrine mechanism between leader cells coordinates their polarization and behaviour under EFs also needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…HB-EGF is a ligand in the epidermal growth factor receptor (EGFR) family [ 5 ], and its expression is mostly enhanced in breast cancer tissues compared to other EGFR ligands [ 6 ]. Previous studies have shown that HB-EGF plays a crucial role in mammary carcinoma, especially in promoting angiogenesis, local invasion and tumor metastasis [ 5 , 7 ]. Moreover, the elevated expression of HB-EGF is correlated with a higher histological grade, higher rate of lymph node metastasis and worse overall survival in breast cancer patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that HB-EGF plays a crucial role in mammary carcinoma, especially in promoting angiogenesis, local invasion and tumor metastasis [ 5 , 7 ]. Moreover, the elevated expression of HB-EGF is correlated with a higher histological grade, higher rate of lymph node metastasis and worse overall survival in breast cancer patients [ 6 , 7 ]. Furthermore, HB-EGF promotes cancer development in association with proangiogenic platelet-derived growth factors (PDGFs) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%